Technology Enhanced Teaching and Professional Staff Development - Divya Singh; Sheryll Kisten (Journal of Ethics in Higher Education)
Academic digital competence in this age of technology is one of the most important considerations for higher education institutions globally. Overall, as higher education institutions increasingly pivot to online learning, academics must keep up with the new trends and developments as new tools and systems reshape their classroom. However, a critical challenge emerging in the literature is the limited support provided to academics to make this transition. This paper canvases the ethical responsibility of higher education institutions to ensure that staff are adequately trained where online teaching is the approved model for learning.